Ethnic difference in serology of Helicobacter pylori CagA between Japanese and non-Japanese Brazilians for non-cardia gastric cancer - Tatemichi, Masayuki; Hamada, Gerson Shigeaki; Nishimoto, Inês Nobuko; Kowalski, Luiz Paulo; Iriya, Kiyoshi; Rodrigues, Joaquim Josê Gama; Tsugane, Shoichiro (Cancer science, 2003)
The usefulness of serology against CagA of Helicobacter pylori as a biomarker to identify high‐risk individuals for non‐cardia gastric cancer (ncGC) remains unclear among several ethnic populations with a high prevalence of cagA‐positive strains. We investigated ethnic differences of CagA serology in two sets of case‐control subjects, Japanese‐Brazilians (JB) and non‐Japanese Brazilians (NJB). We performed a cross‐sectional comparison of IgG antibody titers to CagA (CagA‐Ab) and the combination of CagA‐Ab with conventional surface antigen (Hp‐Ab) in 80 JB and 178 NJB ncGC patients and their controls (160 JB and 178 NJB). The level of CagA‐Ab titer in cancer cases was significantly higher in NJB than in JB. The strength of the association between CagA‐Ab seropositivity (+) (>10 U/ml) and ncGC was almost 2‐fold higher in NJB than in JB [odds ratio (OR) (95% confidence interval), 4.5 (2.6–7.8) and 2.1 (1.2–3.6), respectively]. However, in both JB and NJB, the OR was highest in CagA‐Ab(+) subjects with low titer (10–29 U/ml), and decreased inversely with elevating CagA‐Ab titer. In addition, the serological status of CagA‐Ab(+) and Hp‐Ab(‐) showed a similar close association with ncGC between JB and NJB [5.4 (1.9–15.3) and 5.4 (2.0–15.0), respectively]. These results suggest that although the roles of CagA in the carcinogenic process of ncGC might be different between JB and NJB, the CagA‐Ab could be a useful marker for ncGC, independently of ethnicity, particularly in high‐risk individuals with the serological status of CagA‐Ab(+) with low IgG titer or combined with Hp‐Ab(‐). (Cancer Sci 2003; 94: 64–69)